Determination of potassium fertilizer requirement of maize hybrid with high K availability in the soil. Issue 1 (April 2020) - Herawati,; Syafruddin,
Abstract: Fertilization of K is to be required to increase the productivity of maize besides fertilization of N and P. Therefore, it must be given potassium with the right dosage to fill up the requirement of potassium for maize. This objective of this study was to determine the requirement of K fertilizer of maize hybrid at high K availability in the soil. This research was conducted at the Experimental Farm of Bontobili, Gowa from February - June 2017. This research was arranged in a split-plot design with three replication. The main plot was varieties of hybrid maize i.e. Nasa-29, Bima-4, and Bima-20. The subplots were the dose of potassium fertilizer that consisted of 0, 20, 40, 60, 80, and 100 kg K2O ha −1 . The results of this research showed that optimal K fertilizer for better plant growth and yield attribute was found 20-100 kg K2O ha −1 . Recommendation of K fertilizer depending on yield attainable. If attainable yield > 11 t/ha, recommended K fertilizer was 55 - 66 kg K2O ha −1 . a, but if attainable yield <10 t/ha it was not needed K fertilizer. We suggested to preventing a decrease in the availability of potassium nutrients in the soil, prevented decreasing productivity, and to kept sustainability productivity was requires maintenance of K fertilizer.